Faktor-Faktor Yang Mempengaruhi Tingkat Kemiskinan di Provinsi Jawa Timur - Dwi Bagus Mei Alfianto; Nanik Istiyani; Teguh Hadi Priyono (UPT Penerbitan Universitas Jember, 2019)
Development must be done in an integrated and sustainable, one of them with direct development on areas that have a low level of well-being so that the problem of poverty level can be resolved. This research aims to know the magnitude of the influence of population, human development index (HDI) and gross Regional domestic product (GDP) against the level of poverty in East Java province. This study uses secondary data in the form of poverty levels, population, human development index (HDI) and gross Regional domestic product (GDP) in 10 regencies in East Java province which includes the Districts of Sampang, Bangkalan Regency Regency Probolinggo Regency, Sumenep, Pamekasan Regency of Tuban, Bojonegoro, district of Pacitan Regency, the districts of Wonogiri and Lamongan which has the highest rate of poverty in East Java province year 2010-2015. With the analysis tools used is regression of the data panel. The results of this research show that the panel data analysis tools with the population and human development index (HDI) has a negative influence and significantly to the level of poverty in East Java province year 2010 – 2015, while Domestic Products (GDP) gross regional influence positively and significantly to the level of poverty in East Java province year 2010 – 2015. Keywords: Human Development Index (HDI), Population, Gross Regional Domestic Product (GDP), The Level of Poverty.